Mitigating Drought Impacts in Drylands : Quantifying the Potential for Strengthening Crop- and Livestock-Based Livelihoods - Carfagna, Federica; Cervigni, Raffaello (Washington, DC: World Bank, 2018)
Drylands account for three-quarters of Sub-Saharan Africa's cropland, two-thirds of cereal production, and four-fifths of livestock holdings. Today frequent and severe shocks, especially droughts, limit the livelihood opportunities available to millions of households and undermine efforts to eradicate poverty in the drylands. Prospects for sustainable development of drylands are assessed in this book through the lens of resilience, understood here to mean the ability of people to withstand and respond to droughts and other shocks. An original model was developed expressly to consistently and coherently evaluate different type of interventions on the ground, which provided a common framework to anticipate the scale of the challenges likely to arise in drylands, as well as to generate insights into opportunities for addressing those challenges.